Reinterpreting qiwāmah in Qur’an 4:34: Integrating critical hermeneutics and maqāṣid al-Sharīʿah for gender justice - Ihya' Ulumudin; Aswadi Aswadi; Abu Bakar; Faiqotul Mala; Moch. Mahsun; Raihan Nasir (Institute for Research and Community Service, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, East Java, Indonesia., 2026)
This study examines the interpretation of QS. An-Nisā’ [4]:34, particularly the concept of qiwāmah, and its implications for gender relations in Muslim societies. It seeks to address the tension between classical hierarchical interpretations and contemporary reformist interpretations oriented toward gender justice. Using a qualitative approach, this study integrates comparative exegetical analysis, Nasr Hamid Abu Zayd’s critical hermeneutics, and Jasser Auda’s framework of maqāṣid al-sharīʿah. The analysis focuses on Tafsīr Ibn Kathir and Tafsīr al-Manār as representations of classical and reformist exegetical paradigms. The findings reveal a significant transformation in the interpretation of qiwāmah, from male authority and hierarchical leadership toward ethical responsibility and relational accountability. Similar shifts are also found in the reinterpretation of nushūz and ḍaraba, reflecting a stronger emphasis on justice, human dignity, and the prevention of harm. The hermeneutical analysis shows that both interpretations are shaped by their respective socio-historical contexts, while the maqāṣid-based evaluation indicates that neither paradigm fully satisfies the demands of contemporary gender justice. Based on these findings, this study reconstructs qiwāmah as an ethical-relational responsibility grounded in justice, human dignity, mutual accountability, and non-violence. The originality of this study lies in integrating comparative exegetical analysis, critical hermeneutics, and maqāṣid-based evaluation into a unified framework for reinterpreting qiwāmah and advancing gender justice in contemporary Islamic thought.